Effect of racetrack surface on glycolytic activity of trained endurance horses - Moreira Bogossian, P.; Di Filippo, P. A.; Rafaell Correia-Oliveira, C. R. (International Journal of Performance Analysis in Sport, 2021)
No study has analysed the effects of wet and dry racetrack surface on the glycolytic activity of Arabian horses. The aim of the present study was to investigate the effects of wet and dry racetrack surfaces during a riding test in an Arabian endurance horse. Using a counterbalanced design, nine healthy and trained mixed-bred Arabian horses performed a single-step riding test on a wet (compacted sand) or dry (uncompacted sand) racetrack surface. The wet racetrack received a daily wetting and was compacted using a tractor, while the dry racetrack was upturned by a tractor daily. Both racetracks were elliptical with straight lines of 600 m and total length around 900 metres. Blood samples were drawn from the jugular vein, immediately after the end of the test, and used for the analysis of blood lactate concentration. Mean blood lactate concentration was significantly higher after the riding test on the dry racetrack (2.6 ± 1.6 mmol/L) compared with wet racetrack (0.9 ± 0.3 mmol/L) surface (p = 0.007; d = 1.48, [large]; 95%CI = 0.37-2.44). In conclusion, dry racetrack surface increases lactic anaerobic contribution in trained Arabian horses during a single-step riding test in the field.